Emergence and transcendence in Philip Calyton: His Moderate Ideas Place Him in an Ideal Position for Dialogue - Leach , Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2008)
In his book Mind & Emergence, Philip Clayton explores the relationship between the emergentist vision of the human mind and the question of transcendence. The ongoing explosion of scientific knowledge in the 21st century will tempt many to conclude that no knowledge can exist beyond the boundaries of natural science, only opinion and sentiment. The debate presented by Clayton regarding emergence aims to offer one (although not the only) way of demonstrating that the equation between knowledge and natural science is far from exact. Our perception of there being any true knowledge when the issues at hand go beyond that which can be empirically proven by science may be tenuous. There are certain areas of knowledge, over and above the strict dividing line established by physics and biology, which remain open and which influence life.